(untitled) (Research, Society and Development, 2022)
The impacts of the pandemic in the world were several, among them, the health of health professionals. Further studies are needed to investigate how these workers were affected and what measures are needed to create effective interventions. The objective of the study is to evaluate the impact of the pandemic on the mental health of health professionals in the face of the COVID-19 pandemic. This is a qualitative study, carried out with health professionals working in basic health units and in a university hospital during the peak pandemic period. Individual interviews were carried out using a virtual sample characterization questionnaire, in addition to questions directed to the topic under investigation. The analysis of the collected data followed the scheme: pre-analysis, exploration of the information and treatment of the results. The study highlights the impact experienced in the work routine and personal life of health professionals, during the pandemic scenario, with emphasis on the feelings and changes experienced, such as social distancing, deaths, work overload and lack of PPE, which generated the feeling of uncertainty, apprehension, panic, anxiety attacks, loneliness, among others. It is concluded that public policies are necessary, in addition to the implementation of psychological monitoring programs that can contribute to the prevention of psychological pathologies and help in coping with anguish.